Kinematic, microphysical and latent heating aspects of two mesoscale convective systems observed during TRMM-LBA - Williams, Andrea G., author (Colorado State University. Libraries, 2002)
Dual-Doppler and multiparameter radar data were used to study the environmental atmospheric conditions, kinematics, microphysics, and latent heating characteristics for two tropical mesoscale convective systems (MCSs) observed in the Amazon during the TRMM-LBA field campaign. Each MCS occurred in a different meteorological regime as classified by the low-level zonal wind direction; 17 February 1999 occurred during a period of easterly wind and 23 February 1999 during a period of westerly wind. The data were objectively partitioned into convective and stratiform components and the water and ice masses were determined via the difference reflectivity method. Temporal changes in these quantities allowed for an observationally based diagnosis of latent heating rates for each case. Tropospheric parameters such as larger CAPE, drier air aloft and stronger shear likely contributed to the more intense and more organized system of 17 February 1999. This easterly case contained strong updrafts (> 20 m s-1), differential reflectivity columns extending 1-2 km above the freezing level, and some linear depolarization ratio "caps" above those columns indicating active mixed phase regions. Riming occurred in these mixed phase regions when trends in the mean convective vertical velocities approached local maximums. Approximately twice the amount of total water mass was found in the easterly case compared to the westerly case, in part because there was more convective echo associated with that storm. The westerly case also contained intense convection, strong updrafts (> 15 m s·1), differential reflectivity columns extending slightly above the freezing level, and some weak linear depolarization ratio "caps." Volume total masses involved in riming processes in the westerly case were approximately 75% less than in the easterly case. The latent heating rates for both case studies were dominated by the condensation term throughout most of their life cycles. Latent heating rates due to deposition (sublimation) for both cases were of similar magnitude during their growth (decline) stages. The heating rates due to freezing, melting and riming were inconsequential as their values were 2-3 orders of magnitude smaller. The convective latent heating rates were positive throughout the troposphere while the systems were mature. The stratiform components had much smaller values and less interpretable signals. However, the deposition sub-component for the westerly case remained positive showing that stratiform processes did heat the troposphere above 6.5 km AGL throughout the event. Bulk profiles of the latent heating rates in degrees day"1 per cm day°1 yielded maximums between 4-6 km with shapes very similar to several modeling and budget studies that examined Q1, the apparent heat source term dominated by latent heating.
Spring 2002.
Also issued as author's thesis (M.S.) -- Colorado State University, 2002.
Keywords: Convection (Meteorology) -- Tropics; Mesometeorology -- Tropics